Synthesis and light triggered release of catecholamines from pyrenylmethyl carbamate cages - Fernandes, Maria José G. (2013)
A series of catecholamines (dopamine, norepinephrine, tyramine and octopamine) and their corresponding amino acid precursors in the biosynthetic pathway, L-phenylalanine, L-tyrosine and L-3,4-dihydroxyphenylalanine (DOPA), were reacted with 1-hydroxymethylpyrene in the presence of N,N´-carbonyldiimidazole (CDI). Photolysis studies on the corresponding carbamate conjugates were carried out under irradiation at different wavelengths (250, 300, and 350 nm), followed by HPLC/UV, with the aim to evaluate the applicability of the N-pyrenylmethoxycarbonyl group as a photolabile protecting group for the amino function of neuroactive amines and amino acids. It was found that the carbamate bond between the catecholamine and the pyrenylmethoxycarbonyl unit cleaved readily with the results obtained by irradiation at 350 nm being promising for practical applications.